A Model of Internal Audit in the Company Management System - MUKHINA, Albina (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
An issue of justification of elements of the internal audit integrated system, development of its model focus upon the increased enterprise management efficiency, as well as its inclusion into the management system are believed to be debatable and have to be solved both within a particular enterprise, and at the state level. As a result of the analysis of approaches to definition of internal audit in the scientific and educational literature, the author determined several problematic issues regarding interpretation of the internal audit essence. A model of the internal audit system for self-identification in the enterprise management system is developed to improve the internal control efficiency; a model implementing a comprehensive approach focused upon achieving corporate goals is offered.